Prestação de serviços de desospitalização para idosos na dimensão qualidade percebida em operadoras de saúde e seus impactos n satisfação do beneficiário - Lopes, Donizetti da Silva (2019)
To evaluate the satisfaction of the elderly with a network referenced in the home care, is a success factor in the provision of health services, the investigation of satisfaction levels, allows to apprehend the view of the elderly and their families about the services that are being provided by the network referenced after hospital discharge at his residence. So that this service can be offered Law 13.003 of 2014, which reinforces the obligation of the existence of contracts signed between the operators of plans and hospitals, clinics, autonomous health professionals, diagnostic imaging services and laboratories that make up their referenced network for document and formalize the relationship between these parties. In addition to the object and nature of the contract, there must be the quality of the service provided to the beneficiary in its adequate treatment, either in hospital admission or after discharge to residence with the intuition of promoting satisfaction (ANS). Home care requires the commitment of all professionals during the execution of the daily tasks, achieving this commitment is one of the main challenges of the managers who provide the service for the Elderly Care Program (PAI). Given this context, the general objective of the research, of a descriptive and quantitative nature, is to analyze the satisfaction and quality perceived by the beneficiaries of health care providers. The chosen method was the instrument validated by the SERVQUAL scale. The data were collected from a questionnaire sent by Google Forms to the relative of the elderly, its interpretation was through the analysis instrument contained in the questionnaires and the secondary documents surveyed. The study contributed to the evaluation requirements of the providers of the dehospitalization services, allowing the dehospitalization service managers to identify the critical factors in the provision of home services and propose effective improvement and innovation of the practice of care to be administered to the elderly.